An Exploration of the Experiences of Informal Caregivers of Stroke Patients in Saudi Arabia; A Qualitative Study - Afnan Yousef Tunsi PhD, MSc, BSN, RN; Anwar Tammar BSN, RN; Jood Wahbah BSN, RN; Fatimah Al-Marhoon BSN, RN; Jomana Al-Mashjary BSN, RN; Marym Alaamri PhD, MSN, BSN, RN; Aisha Alhofaian PhD, MSN, BSN, RN; Ruba Alharazi PhD, MSc, BSN, RN (SAGE Open Nursing, 2025)
Introduction Caregivers play a critical role in improving stroke survivors’ outcomes. Yet, they often encounter numerous challenges in their caregiving process, with the lack of rehabilitative services and poststroke follow-ups. While extensive research has explored caregiver challenges primarily in Western contexts, sociocultural factors significantly influence family caregiving experiences and roles, necessitating exploration within the Saudi cultural context. Objectives This study aimed to explore the experiences of family caregivers of stroke survivors in Saudi Arabia. Method A descriptive exploratory qualitative design was employed. Using purposive sampling, 20 family caregivers of stroke patients were recruited from three healthcare institutions. Data collection involved individual semi-structured interviews complemented by field notes. A thematic analysis approach was used for data analysis. Results Four major themes captured caregivers’ experiences and challenges: (a) emotional and psychological strain, (b) barriers to navigating healthcare systems, (c) disrupted daily living and social isolation, and (d) resilience through coping mechanisms. Conclusion This study enhances the understanding of caregivers’ experiences of stroke survivors in Saudi Arabia. While the findings are aligned with global literature, they also reveal culturally specific challenges and coping mechanisms that are unique to the Saudi context. These insights underscore the need for culturally sensitive practices, including caregiver education, mental health support, and community-based services. To improve continuity of care and caregiver well-being, healthcare policies should prioritize integrated support systems and long-term care planning tailored to family-centered models of caregiving.